An evolution of entrepreneurial culture studies: A systematic literature review and future research agenda - Quoc Hoang Thai; Mai Ngoc Khuong (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: The objective of the article is to review entrepreneurial culture (EC) literature by seeking, analysing, and synthesising the research findings of extant journal articles. This study aims to demonstrate the evolutionary trends and current trends in EC research, which cannot be found in extant literature reviews of EC due to the limited number of analysed articles which focused only on the associations between national EC (NEC) and entrepreneurship. Research Design & Methods: This research employed a systematic literature review (SLR) approach. The research technique of Garrard (2004) was utilized to create an SLR matrix to analyse the EC literature in peer-reviewed English journal articles. This study gathered and analysed 83 publications in 57 journals in the period between 1992 and 2021. Findings: The article proposes four essential outcomes as the results of integrating the information that was investigated and approved in the literature. Firstly, there is an extreme development tendency in the number of EC articles which started rapidly in 2012. Secondly, this study offers the holistic framework of NEC which is the combination of five forms or indications including needs and motives, beliefs and behaviours, cognition, cultural values (societal and individual levels), and social context; while organizational entrepreneurial culture (OEC) is a unidimensional construct or a combination of the organizational characteristics that stimulates, promotes, and sustains the entrepreneurial activities of the organizations. Thirdly, this research generated two nomological networks that recapitulate and display the causal relationships of both veins of EC, which can be employed and expanded to enrich institutional theory and social cognitive theory. Finally, it provides promising research areas for future EC research in terms of research context, research design, theory, framework, measurement, and nomological network of NEC and OEC. Implications & Recommendations: These findings provide meaningful implications for both theory and practice. In the theoretical context, we integrated and described the most recent and exclusive trends, frameworks, theories, measurements of both veins of EC and their causal relationships, and the research guideline for further research, thus, contributing to the theoretical development in EC literature. In a practical context, two nomological networks of EC contribute to the positive perceptions, awareness, and acknowledgement of the importance of developing and sustaining an appropriate EC amongst individuals, organizations, and nations. Contribution & Value Added: This research integrates and demonstrates the most recent and exclusive trends, frameworks, theories, and measurements of EC and their causal relationships, proposing the research guideline for further studies. By offering the evolutionary trend of EC articles, this study provides evidence for selecting a suitable methodology through which future research can be conducted to create novel knowledge to develop the EC field. This study offers the holistic frameworks and two nomological networks of NEC and OEC that can be leveraged to enlarge the institutional theory and social cognitive theory, resolving the problems of disintegration and disjointedness that emerged in the literature.
Keywords: L26; M13; 330; entrepreneurial culture; entrepreneurship culture; entrepreneurial climate; entrepreneurial environment; systematic literature review